2020
DOI: 10.1111/jpn.13287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of purified fibre‐mixture supplementation of gestation diet on gut microbiota, immunity and reproductive performance of sows

Abstract: This experiment was conducted to investigate the effects of a purified fibre‐mixture (FM, 50% guar gum, 50% cellulose) supplementation of gestation diet on the immunity, faecal microbial composition and reproductive performance of sows. A day after breeding, 68 multiparous sows were randomly allocated to receive treatment with a control (CON) diet or a diet containing 3% FM (FM diet). Results showed the FM diet to be associated with a significant increase in the number of live‐born piglets relative to CON (13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Dietary fiber is the main source of energy for gut microbiota, which means that adding an appropriate amount of dietary fiber can increase the abundance of specific microorganisms ( Sappok et al., 2015 ). In addition, dietary fiber also increases the proportion of beneficial bacteria and reduces the proportion of pathogenic bacteria in the gut ( Guan et al., 2019 ; Jiang et al., 2019 ; Wu et al., 2020 ; Xu et al., 2020a ).…”
Section: Dietary Fiber Regulates the Abundance And Diversity Of Sow Gmentioning
confidence: 99%
See 3 more Smart Citations
“…Dietary fiber is the main source of energy for gut microbiota, which means that adding an appropriate amount of dietary fiber can increase the abundance of specific microorganisms ( Sappok et al., 2015 ). In addition, dietary fiber also increases the proportion of beneficial bacteria and reduces the proportion of pathogenic bacteria in the gut ( Guan et al., 2019 ; Jiang et al., 2019 ; Wu et al., 2020 ; Xu et al., 2020a ).…”
Section: Dietary Fiber Regulates the Abundance And Diversity Of Sow Gmentioning
confidence: 99%
“…Short-chain fatty acids involved in the regulation of sow metabolism, immunity, and cell proliferation ( Li et al., 2019 ; Wu et al., 2020 ; Xu et al., 2020a ). Dietary supplementation of 3% purified fiber-mixture significantly increase the concentrations of butyrate and propionate in the feces of sows, which was related to the increase in the abundance of Eubacterium-hallii-group and Bacteroides in the gut ( Wu et al., 2020 ). Different types of dietary fiber contribute to the variation of SCFA ( Tokach et al., 2019 ).…”
Section: Biological Effects Of Dietary Fiber Fermentation By-productsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they found that elevating the proportion of fiber in the diet increases the α-diversity and β-diversity indices of the porcine gut microbiota [ 102 ]. Importantly, dietary fiber supplementation not only upregulates the proportion of beneficial bacteria but also diminishes the proportion of pathogenic bacteria in the gut [ 114 , 115 , 116 ], which may be conducive to the improvement of intestinal health and meat quality of pigs [ 117 , 118 ]. Nevertheless, dietary fiber from different sources has been investigated to have different effects on microbial composition and diversity.…”
Section: Factors Affecting Gut Microbial Composition and Functionmentioning
confidence: 99%